A Design of Proposed Dashboard Model for Researchers in Social Research Network Sites - Siti Hawa, Apandi; Ruzaini, Abdullah Arshah (2015)
Many researchers have used online platform such as social research network sites (SRNS) for their research works. The researchers want to be notified on latest information in research field. However, there are huge amounts of information in the SRNS to be handled. The researchers need a dashboard as a tool to provide awareness on current information in research field to the researchers. This paper aims to discuss on the design of a dashboard model for the researchers in the SRNS. The dashboard model consists of the dashboard components that are used to satisfy the researcher needs. The proposed dashboard components are identified based on analysis from literature studies and by review on the current SRNS. A survey was conducted in order to verify the proposed dashboard components. From the survey, the dashboard components can be grouped into three factors that shared common themes. Then, we construct the dashboard model for the researchers in the SRNS. The dashboard model has three menu categories which are 1)researcher performance for the purpose to measure the researcher performance, 2) research statistics for the purpose to monitor research trends and 3) research events alert for the purpose to alert on upcoming events. The dashboard components are listed based on the three menu categories in the dashboard model.